Exploring Catalytic Activity Modulations: Photoredox Catalysis with Substituted Copper(I)-Dipyridylamine Derivatives - Zuñiga-Loyola, C; Zuñiga-Loyola, C (Royal Society of Chemistry, 2025)
In this work, we have successfully synthesized five new heteroleptic copper(i) complexes (C1-5), bearing N,N ligands derived from dipyridylamine and S-BINAP as the P,P auxiliary ligand. All complexes were structurally characterized using NMR, FT-IR, and elemental analysis. Furthermore, the molecular structures of C1, C4, and C5 were determined via X-ray diffraction analysis. The photophysical properties of all complexes were assessed using UV-Vis spectroscopy and spectrofluorometric measurements in dichloromethane solution and the solid state. All complexes displayed absorption bands at lower energies, attributed to spin-allowed MLCT transitions. In degassed dichloromethane solution at room temperature, all complexes exhibited broad luminescence in the visible spectrum, mainly assigned to MLCT/LLCT phosphorescence, with excited state lifetimes in the μs time regime. Besides, all complexes were assessed as photoredox catalysts in chlorosulfonylation and bromonitromethylation reactions of styrene, showing remarkable performances, thus highlighting the privileged role of the dpa ligand for the design of Earth-abundant metal photocatalysts. © 2025 The Royal Society of Chemistry.